INFESTASI CAPLAK PADA SAPI DI DESA TOLOK KECAMATAN TOMPASO KABUPATEN MINAHASA - Patodo, Gabriel B.; Nangoy, M.J.; Assa, G.V.J.; Lomboan, A. (Universitas Sam Ratulangi, 2018)
INFESTATION OF TICKS ON CATTLE IN TOLOK VILLAGE TOMPASO DISTRICT, MINAHASA. The tick is one of the most commonly encountered ectoparasites on livestock and can degrade its quality and quantity significantly. Risks caused by tick infestation include local skin damage, anemia, paralysis due to toxins, and disease transmission. A research project on tick infestation was conducted for 1 (one) month in Tolok Village of the Minahasa District due to counted the prevalence of tick infestation on cattle, the preference of tick infestation based on body parts, sex and age. The research used the survey method, in which tick samples were collected during the day, preserved in a 70% alcohol solution, and then counted in the laboratory of Faculty of Animal Science, Sam Ratulangi University of Manado. The results showed that tick infestation on cattle in Tolok Village yielded 100% prevalence (all the cattle observed (n=53) were infested by ticks). Infestation preference based on body parts showed the highest on the crotch region (average 6,70 ticks) compared on the head ( average 1,75 ticks ), the neck (average 5,55 ticks), the back ( average 3,4 ticks), 4,44 ticks on the abdomen ( average 4,44 ticks), and the legs (1,11 ticks). Infestation preference based on sex showed the highest on female (32,05 ticks) compared on male (20,65 ticks). Finally, based on the cattles’ age, the infestation preference were a average of 27 ticks on calfs and 26,15 ticks on adult cattles. Higher infestation preference was found in calfs rather than adult cattle.Keywords: Infestation, Tick